Implementation of Character Education for Early Childhood - laela lutfiana rachmah; Raras Ayu Prawinda; Laelatul Azizah; Arif Muzayin Shofwan (Universitas Nahdlatul Ulama Blitar, 2022)
Character education must be implemented in early childhood. This is because early childhood has different characteristics from adults. This descriptive qualitative research with a literature study discusses the implementation of character education for early childhood. The data analysis technique uses content analysis by sorting out data according to the research objectives. This paper produces the following things. First, the characteristics of early childhood so that character education must be implemented because they have several characteristics, namely: unique, egocentric, active and energetic, exploratory and adventurous, relatively spontaneous, easily frustrated, lack of consideration in doing things, short attention span, and passionate. to learn from experience. Second, the values ​​of character education that can be implemented in early childhood include love of God; responsibility, discipline, and independence; honesty; respect and courtesy; affection, care, and cooperation; confidence, creative, hard-working, and never give up; justice and leadership; kind and humble; and tolerance, love of peace, and unity. Third, several things that teachers must do in implementing character education development, among others: treat children according to their characteristics, foster positive understanding, meet basic needs, familiarize children with socializing, patterns of educating teachers and parents must be interrelated, provide support and appreciation, provide age-appropriate facilities, and have a firm, consistent, and responsible attitude.